Peran Teknologi Dalam Optimalisasi Manajemen Organisasi Pendidikan (Jurnal Motivasi Pendidikan dan Bahasa, 2024)
This article conducts a literature review to discuss the role of technology in optimizing school organizational management. The study looks at how technology can improve administration, communication and decision-making in schools. Furthermore, the article discusses the different types of technology that can be used, including school management information systems, e-learning platforms and digital collaboration tools. Challenges and barriers to technology implementation are also discussed, such as infrastructure limitations and lack of technical expertise among school personnel. Then, the article suggests appropriate strategies to overcome such barriers, such as continuous training and integrated system development, in order to improve the overall management of school organizations. This study offers valuable insights for educators and school administrators who want to improve efficiency and effectiveness through the use of technology.